2011
DOI: 10.1128/aem.02617-10
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Highly Heat-Resistant Listeria monocytogenes Variants by Use of a Kinetic Modeling-Based Sampling Scheme

Abstract: Stable high-hydrostatic-pressure (HHP)-resistant Listeria monocytogenes LO28 variants were previously isolated and characterized. These HHP variants were also more resistant to heat. In addition, nonlinear heat inactivation kinetics pointed toward the existence of heat-resistant variants, although these could not be isolated so far. In this study, we used kinetic modeling of inactivation curves of two isolated HHP variants and their wild type, and this revealed that the probability of finding resistant variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…Genotypic heterogeneity refers to the presence of stable stressresistant variants with an inheritable stress-resistant phenotype caused by genomic alterations (6). These stable stress-resistant variants have been repeatedly isolated from the foodborne pathogen Listeria monocytogenes upon exposure to different types of stress, e.g., heat, high hydrostatic pressure (HHP), and low pH (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Genotypic heterogeneity refers to the presence of stable stressresistant variants with an inheritable stress-resistant phenotype caused by genomic alterations (6). These stable stress-resistant variants have been repeatedly isolated from the foodborne pathogen Listeria monocytogenes upon exposure to different types of stress, e.g., heat, high hydrostatic pressure (HHP), and low pH (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…But differences between strains (figures 3.3C, 3.3F, and 3.3I) were much higher than differences between replicates or between reproductions. Moreover, at all temperatures, we observed that strains L6, FBR14, and FBR16 had lower inactivation rates than the other strains, and strains ScottA and LO28, which are often used as model strains (Casadei et al, 1998;Chen and Hoover, 2003;Gaze et al, 1989;Stephens et al, 1994;Sumner et al, 1991;Van Boeijen et al, 2011), were amongst the most heat sensitive strains at 60C and 65C. To estimate the D-value, the inactivation curves were fitted using a modified Weibull model.…”
Section: Thermal Inactivation Kinetics Of L Monocytogenesmentioning
confidence: 95%
“…Although a higher protective effect was given by ham, the D 72 -value of 3 L. monocytogenes strains grown and/or inactivated in ham were calculated to range from 0.5 s to 2 s. When a similar thermal processing for 15 s is applied for ham, the heat treatment will eliminate more than 7 log 10 CFU/g of the bacterial cells. However, Van Boeijen et al (2011) also reported the occurrence of resistant variants with average D 72 value of 3.02 ± 0.21 s, indicating that the current pasteurization process might not be sufficient to inactivate all heat stress robust variants or to meet the 6 log 10 reduction of the performance criterion as described by ILSI Europe. In general, the most important factors to be considered for thermal inactivation, in which each having about equal impact, are strain variability, the presence of resistant fractions in microbial populations, the effect of food matrix and effect of growth history.…”
Section: Variability In Thermal Inactivation Kinetics: the Effect Of mentioning
confidence: 99%
See 2 more Smart Citations